A COMPARATIVE STUDY BETWEEN CONVENTIONAL AND ISLAMIC COMMERCIAL BANKS IN TERMS OF SHAREHOLDERS EFFICIENCY OVER THE PERIOD 2010-2016 - Mukaromah, Latif Zuhriyah; Faturohman, Taufik (Journal of Business and Management, 2017)
Abstract: There a different explanation between the fact and the prediction regarding to the Islamic Banking growth. The fact shows they were good even faster than Conventional Banking but  predicted slow-moving by Karim Business Consulting (KBC) because of small capital and capacity related with shareholder. This research is conducted to provides new insight for decision maker based on the result of shareholders’ efficiency difference between two types of bank, and correlation between shareholders and growth of bank. Methods: This research using Data Envelopment Analysis (DEA) to measure the efficiency since it is the common method, Spearman’s Correlation to analyze the correlation, Mann-Whitney test is applied to obtain statistically significant different. The data is annual report that consist of Balance Sheet and Income Statement of Conventional Banks and Islamic Commercial Bank during 2010-2016 that listed in Otoritas Jasa Keuangan (OJK). Results:  The finding show there were a statistically significant different shareholders efficiency between two types of bank in 2010 and 2012. In 2010 Conventional Banks were more efficient and in 2012 shows the contrary. For both types of bank have a weak correlatin even very weak correlation for Conventional Banks. Conclusion: Islamic Commercial Banks shows a good progress as they starting to catch up the Conventonal Banks efficiency in 2012. But for both types of bank still need to increase the shareholders efficiency since the result shows a weak correlation. Keywords:  Data Analysis Envelopment (DEA);efficiency;growth;Islamic Commercial Banks, Conventional Banks.